2013
DOI: 10.5312/wjo.v4.i3.134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of straight median sternotomy and interlocking sternotomy with respect to biomechanical stability

Abstract: AIM:To increase the stability of sternotomy and so decrease the complications because of instability. METHODS:Tests were performed on 20 fresh sheep sterna which were isolated from the sterno-costal joints of the ribs. Median straight and interlocking sternotomies were performed on 10 sterna each, set as groups 1 and 2, respectively. Both sternotomies were performed with an oscillating saw and closed at three points with a No. 5 straight stainless-steel wiring. Fatigue testing was performed in craniocaudal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Likewise, Kucukdurmaz et al reported that a small, non-zigzag-shaped osteotomy was superior to plain osteotomy. 15 Sinha et al compared the postoperative effects of endonasal and percutaneous osteotomy techniques during rhinoplasty in 45 patients. Endonasal osteotomy has been reported to cause ecchymosis, edema and hemorrhage more frequently when compared to percutaneous lateral osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Kucukdurmaz et al reported that a small, non-zigzag-shaped osteotomy was superior to plain osteotomy. 15 Sinha et al compared the postoperative effects of endonasal and percutaneous osteotomy techniques during rhinoplasty in 45 patients. Endonasal osteotomy has been reported to cause ecchymosis, edema and hemorrhage more frequently when compared to percutaneous lateral osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Kucukdurmaz et al found that interlocking sternotomy (a zigzag cut in three dimensions) is superior to those of the straight median sternotomy [19]. The zigzag cuts made the sternotomy line significantly more stable and provided more surface area for bony healing.…”
Section: Discussionmentioning
confidence: 99%
“…These complications include mediastinitis in 0.3 to 5% of patients, with a mortality rate of 14 to 47% [ 1 ]. Since the sternum is divided, sternal instability is another possible complication, which is the leading cause of postoperative morbidity and mortality [ 2 , 3 ]. These complications can result in a prolonged hospital stay and subsequently a higher healthcare cost [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%